TIMING FOR STEP-DOWN THERAPY OF CANDIDEMIA IN NON-NEUTROPENIC PATIENTS: AN INTERNATIONAL MULTI-CENTER STUDY - Rola Husni; Remie Chrabieh; Rita Wilson Dib; Jose Vazquez, MD; Thaís Guimarães; Ana Fernández; Rita Khoury; Lina Asmar; Georges Khazen; Nadia Lara Samaha; Issam Raad; Ray Hachem (Mediterranean Journal of Hematology and Infectious Diseases)
Background: Candida bloodstream infection (BSI) remains one of the leading causes of BSI in critically ill and immunosuppressed cancer patients. In light of the changing epidemiology and rising resistant species, duration of treatment and appropriate timing of stepdown therapy from intravenous (IV) to oral antifungal agents are crucial for utmost disease control and overall survival.